Callipyge mutation affects gene expression in cis: A potential role for chromatin structure - Murphy, Susan K.; Nolan, Catherine M.; Huang, Zhiqing; Kucera, Katerina S.; Freking, Brad A.; Smith, Timothy P.L.; Leymaster, Kreg A.; Weidman, Jennifer R.; Jirtle, Randy L. (Genome Research, 2006)
Muscular hypertrophy in callipyge sheep results from a single nucleotide substitution located in the genomic interval between the imprinted Delta, Drosophila, Homolog-like 1 (DLK1) and Maternally Expressed Gene 3 (MEG3). The mechanism linking the mutation to muscle hypertrophy is unclear but involves DLK1 overexpression. The mutation is contained within CLPG1 transcripts produced from this region. Herein we show that CLPG1 is expressed prenatally in the hypertrophy-responsive longissimus dorsi muscle by all four possible genotypes, but postnatal expression is restricted to sheep carrying the mutation. Surprisingly, the mutation results in nonimprinted monoallelic transcription of CLPG1 from only the mutated allele in adult sheep, whereas it is expressed biallelically during prenatal development. We further demonstrate that local CpG methylation is altered by the presence of the mutation in longissimus dorsi of postnatal sheep. For 10 CpG sites flanking the mutation, methylation is similar prenatally across genotypes, but doubles postnatally in normal sheep. This normal postnatal increase in methylation is significantly repressed in sheep carrying one copy of the mutation, and repressed even further in sheep with two mutant alleles. The attenuation in methylation status in the callipyge sheep correlates with the onset of the phenotype, continued CLPG1 transcription, and high-level expression of DLK1. In contrast, normal sheep exhibit hypermethylation of this locus after birth and CLPG1 silencing, which coincides with DLK1 transcriptional repression. These data are consistent with the notion that the callipyge mutation inhibits perinatal nucleation of regional chromatin condensation resulting in continued elevated transcription of prenatal DLK1 levels in adult callipyge sheep. We propose a model incorporating these results that can also account for the enigmatic normal phenotype of homozygous mutant sheep.
10.1101/gr.4389306